Sistem Informasi Persediaan Sparepart Mobil pada Bengkel Madani Ban Salakan Kabupaten Banggai Kepulauan - Yeti Kule; Cicila Wati (Jurnal Ilmiah Sistem Manajemen Informatika dan Komputerisasi Akuntansi, 2021)
Bengkel Madani is a company engaged in the sale of spare parts and car repair services. Which was founded in 2010 until now. Inventories and spare parts sales transactions at this time, using a method that is still simple, namely. The cashier will record all spare parts sales transactions in the journal. And will recap the sales reports in a day to be given to the owner. Sometimes errors occur during calculations. Likewise, problems often occur during the process of searching for stock data or spare parts inventory. Which takes a long time to find a match for spare parts and the customer's car. The purpose of this research is to build an application for Car Spare Parts Inventory Information System at the Ban Salakan Bengkel Madani, Banggai Islands Regency, using the Java programming language and MySQL as data storage media. Data collection methods used are field methods, interview methods and library methods. In this research, an Information System for Car Spare Parts Inventory has been successfully built at the Ban Salakan Civil Service Workshop, Banggai Islands Regency.